Governmentality and surf tourism destination governance. Issue 11 (2nd November 2018) - Mach, Leon; Ponting, Jess
Abstract: Surf resources are critical to thousands of coastal communities as the natural resource base for many tourism services that spur development. There is, however, almost a total lack of formal surf-break management around the world, despite many surf resources becoming crowded, which leads to nuanced resource conflicts with social, economic and environmental implications. Managerial approaches and surf research, we argue, could become more effective by incorporating a nuanced understanding of the scales and process that govern behavior in surf tourism. This conceptual article first applies tourism destination governance (TDG) to outline the many stakeholders and scalar dimensions involved in governing surf tourism. To expand this normative analysis, Foucault's governmentality framework is used to discuss different informal governance regimes (sovereign, disciplinary, and neoliberal) that conduct behavior at surf-breaks. The intersection of TDG and typologies of governmentality then help to discuss empirical cases demonstrating how governmentalities operating both at the surf-break and at wider scales, often overlap to either reinforce one another and powerfully condition behavior or compete and make governance ineffectual. This elaboration of surf tourism destination governance (STDG) opens up a new research agenda for surf tourism scholarship also applicable to other forms of tourism dependent upon contested natural resources.